Photon reconstruction in the ATLAS Inner Detector and Liquid Argon Barrel Calorimeter at the 2004 Combined Test Beam - Onofre, A. (2011)
The reconstruction of photons in the ATLAS detector is studied with data taken during the 2004 Combined Test Beam, where a full slice of the ATLAS detector was exposed to beams of particles of known energy at the CERN SPS. The results presented show significant differences in the longitudinal development of the electromagnetic shower between converted and unconverted photons as well as in the total measured energy. The potential to use the reconstructed converted photons as a means to precisely map the material of the tracker in front of the electromagnetic calorimeter is also considered. All results obtained are compared with a detailed Monte-Carlo simulation of the test-beam setup which is based on the same simulation and reconstruction tools as those used for the ATLAS detector itself.